Mindful learning through mindfulness bells as a predictor to improve student learning outcomes - Reni Reni; Vike Aprilianin Marwintaria Saputri; Sidartha Adi Gautama (Universitas Sebelas Maret, 2025)
This study was motivated by the importance of improving student learning outcomes through a learning approach that not only focuses on cognitive aspects but also shapes students' awareness, attitudes, and positive behaviour. This study aims to determine the effect of mindful learning on improving student learning outcomes with mindful bells at Buddhist Sunday School (BSS) Dharma Gaya, Metro City. Mindful Learning is a learning approach that emphasises full awareness in the learning process. Students are encouraged to be fully present, aware, and focused on every activity they do. Mindful bells are used as a tool to help students direct their attention to learning in a calmer and more focused manner. This study used a quantitative approach with a survey method involving 45 students as the overall subjects of the study. The research instrument used was a questionnaire with a Likert scale that measured mindful learning with mindful bells. Simple linear regression analysis was used to test the research hypothesis, and SPSS (Statistical Package for the Social Sciences) for Windows version 26 was used as a tool to analyse the data. The results showed that there was a positive and significant influence of 65.5% between the variables of mindful learning with mindful bells and the improvement in student learning outcomes at BSS Dharma Gaya Kota Metro. Meanwhile, the remaining 34.5% was influenced by other factors not included in the study. This means that the better the application of mindful learning with mindful bells in learning activities, the more it will improve student learning outcomes as shown by changes in the cognitive, affective, and psychomotor aspects of students.